Toward Characterizing Dark Matter Subhalo Perturbations in Stellar Streams with Graph Neural Networks - Peter Xiangyuan Ma; Keir K. Rogers; Ting S. Li; Renée Hložek; Jeremy J. Webb; Ruth Huang; Julian Meunier (The Astrophysical Journal, 2025)
The phase space of stellar streams is proposed to detect dark substructure in the Milky Way through the perturbations created by passing subhalos—and thus is a powerful test of the cold dark matter paradigm and its alternatives. Using graph convolutional neural network (GCNN) data compression and simulation-based inference (SBI) on a simulated GD-1-like stream, we improve the constraint on the mass of a [10 ^8 , 10 ^7 , 10 ^6 ] M _⊙ perturbing subhalo by factors of [11, 7, 3] with respect to the current state-of-the-art density power spectrum analysis. We find that the GCNN produces posteriors that are more accurate (better calibrated) than the power spectrum. We simulate the positions and velocities of stars in a GD-1-like stream and perturb the stream with subhalos of varying mass and velocity. Leveraging the feature encoding of the GCNN to compress the input phase space data, we then use SBI to estimate the joint posterior of the subhalo mass and velocity. We investigate how our results scale with the size of the GCNN, the coordinate system of the input, and the effect of incomplete observations. Our results suggest that a survey with 10× fewer stars (300 stars) with complete 6D phase space data performs about as well as a deeper survey (3000 stars) with only 3D data (photometry, spectroscopy). The stronger constraining power and more accurate posterior estimation motivate further development of GCNNs in combining future photometric, spectroscopic, and astrometric stream observations.